Gastronomy: An Econometric Analysis as a Business Driver / Tricia Anne Jimenez Tipon and Maria Victoria Rosas - Jimenez Tipon, Tricia Anne; Rosas, Maria Victoria (Universiti Teknologi MARA Cawangan Kelantan, 2020)
Gastronomy has evolved from being just sustenance to a human being’s basic need into now, satisfying experiences and the soul. Its evolution has brought about new sectors, new products, and new partnerships. It has shifted from just a supporting sector of one of the world’s strongest economic performers, tourism, to becoming a new separate sector, gastronomic tourism where there is a significant research gap in its context. The study conducted an econometric analysis on gastronomy as a business driver and proposed a gastronomic model. It further provided accounts on its viability as a tourism destination. Trend analysis was performed to evaluate, analyze, and describe its status vis a vis significant relationships and differences. Primary data covered the local gastronomic business providers’ and tourists’ surveys in Negros Island, Philippines, while the secondary data came from the tourist arrivals and tourist receipts from 1997-2017. The business providers comprised of restaurants, food entities, and food businesses and the selection of these respondents was based on a predetermined criteria established from the inputs of industry experts and tourism officers which included top cuisines – specific local dishes; top food items – specific “pasalubong” (a small gift usually food given to friends or relatives when returning from a trip) items; and top food destinations – particular restaurants. The gastronomic products were categorized into three main attributes; Food, Beverage, and Culture. Findings included Food was the primary motivator and business driver for business providers